Teacher-Centered Systemic Reform Model: An Exploration of the Contributing Factors to Science Teachers’ Adoption of Inquiry-Based Pedagogy - Monday Moju; Nation Ibetobou John; Chiamaka Nneka Oguejiofor (Scientia Publica Media, 2026)
Inquiry-based pedagogy is a constructivist-based student-centered instructional approach that facilitates learners’ active construction of knowledge through exploration and questioning. Recognized in national curricula, such as the Framework for K-12 Science Education, this approach has been identified as a powerful strategy to achieve the goal of science education: preparing scientifically literate citizens capable of addressing societal challenges. Despite its benefits, prior research highlights the slow adoption of inquiry-based pedagogy among science teachers, limiting meaningful teaching and learning opportunities for learners. This study investigates the factors influencing teachers’ adoption of inquiry-based pedagogy through the lens of the Teacher-Centered Systemic Reform (TCSR) model in the Nigerian context. Employing a survey research design, data were collected using a structured questionnaire distributed via Google Forms to science teachers across Lagos State, Nigeria, with 206 respondents filling out and returning the survey. Descriptive and regression analyses of the data revealed that among the variables considered, only years of teaching experience significantly predicted teachers’ adoption of inquiry-based pedagogy (β =0.91, p< 0.005). Other variables, including teacher responsibility, support, classroom management, and teacher thinking, were found to be statistically insignificant. These findings prompted a deeper exploration of potential reasons for their lack of significance, shedding light on systemic challenges within the educational landscape that science teachers have surmounted over the years. The study suggests the need for the Nigerian education system to prioritize creating an enabling environment that empowers teachers at all experience levels to embrace innovative, student-centered pedagogical practices that meet the demands of 21st-century education.